Tinjauan Ekonomi Syariah terhadap Risiko Riba dalam Skema Investasi Emas - Imam Mawardi; Dila Istianah (SAUJANA : Jurnal Perbankan Syariah dan Ekonomi Syariah, 2026)
This study aims to analyze the level of compliance with sharia economic principles and evaluate the potential risk of usury (riba) in gold investment schemes at Pegadaian Syariah (Islamic Pawnshop). Gold investment is a popular financial instrument due to its characteristics as a hedge against inflation. However, from a fiqh muamalah perspective, gold transactions fall into the category of usurious goods, requiring the fulfillment of specific provisions to avoid usury practices. This study uses a qualitative approach with a case study method, as well as a normative analysis of operational practices, types of contracts applied, and transaction mechanisms for gold savings and gold installment products. The results show that gold investment practices at Pegadaian Syariah generally comply with sharia principles through the implementation of murabahah, rahn, and wadiah contracts, as well as supervision by the Sharia Supervisory Board. However, potential risks of usury (riba) can still arise in aspects of administrative costs, late payment penalties, and customer understanding of the concept of sharia-compliant gold ownership. This study emphasizes the importance of strengthening sharia financial literacy and information transparency to ensure gold investment practices remain consistent with the objectives of maqashid sharia.